A note on a decision support system for multiobjective integer and mixed-integer programming problems - Alves, Maria João (2004)
This note presents the main characteristics of a decision support system (DSS) dealing with multiobjective integer and mixed-integer programming problems. The DSS is based on interactive reference point approaches developed by the authors for this kind of problems. It is implemented for Windows platforms and aims at providing an open communication protocol for interaction with the decision maker(s).